Differences between quality of life and occupational coping of tenured and outsourced nurses - Cynthia Lima Sampaio; Paulo César de Almeida; Ângela Maria Alves e Souza; Maria Fabiana de Sena Neri; Leonardo Alexandrino da Silva; Joselany Áfio Caetano (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: To compare the relation of quality of life to occupational coping and verify the association of these indicators with sociodemographic variables of tenured and outsourced nurses. Methods: Cross-sectional study, carried out from June to November 2014, with 145 outsourced nurses and 45 tenured nurses. We applied an identification instrument (WHOQOL-bref) and Occupational Coping Scale. Student's t-tests and Pearson's correlation coefficient were used. Results: Tenured nurses had better quality of life (p=0.011) and a mean in the Avoidance factor with a strong correlation (p=0.001). Female public servants (p=0.006; p<0.0001), between 40 and 66 years old (p=0.005; p=0.031), specialists (p=0.028; p=0.005), with a family income from 2.5 to 6.8 minimum wages (p=0.021; p=0.006) and working in the morning or afternoon (p=0.043; p=0.020) and morning and afternoon (p=0.038; p=0.007) showed a difference in quality of life and in Avoidance factor, respectively. Conclusion: Tenured nurses demonstrated better quality of life, and some variables trigger differences in the groups, demonstrating the need to promote occupational health.